Azerbaijan and European Higher Education Area: Students’ Involvement in Bologna Reforms - Mammadova, Lala; Valiyev, Anar (Research in Educational Administration & Leadership, 2020)
This study explores the progress of the 14-year old Bologna reform in major Azerbaijani public universities. The focus of the study was to investigate the level of student involvement in the transformation process of the European Higher Education Area. The data for the research were collected from a survey conducted among 2,400 bachelor’s and master’s students, as well as through semi-structured interviews with university administrators and experts. The study mainly examines the key elements of Bologna process – degree structure, quality assurance, mobility, and social dimension. The study found that despite the remarkable progress in the development of higher education system in the country, much work still needs to be done at the institutional level to involve students in all stages of the reform process. Huge discrepancies and shortages are observed with respect to the role of students in the quality assurance process both at the external and internal level. In terms of the internationalization of institutions, formal strategies and targets, as well as sufficient funding, are not yet fully existent in higher education institutions. Meanwhile, students in the chosen universities are either unaware of student support services or unsatisfied with the provision of those services.
Keywords: Azerbaijan -- Education.; Education, Higher -- Aims and objectives -- Azerbaijan.; Bologna process -- Azerbaijan.